Can we enhance osteoporotic metaphyseal fracture healing through enhancing ultrastructural and functional changes of osteocytes in cortical bone with low‐magnitude high‐frequency vibration?. Issue 3 (21st January 2020) - Choy, Man‐Huen Victoria; Wong, Ronald Man‐Yeung; Li, Meng‐Chen; Wang, Bai Yan; Liu, Xiao Dong; Lee, Wayne; Cheng, Jack Chun‐Yiu; Chow, Simon Kwoon‐Ho; Cheung, Wing‐Hoi
Abstract: Fragility fractures are related to the loss of bone integrity and deteriorated morphology of osteocytes. Our previous studies have reported that low‐magnitude high‐frequency vibration (LMHFV) promoted osteoporotic fracture healing. As osteocytes are known for mechanosensing and initiating bone repair, we hypothesized that LMHFV could enhance osteoporotic fracture healing through enhancing morphological changes in the osteocyte lacuna‐canalicular network (LCN) and mineralization. A metaphyseal fracture model was established in female Sprague‐Dawley rats to investigate changes in osteocytes and healing outcomes from early to late phase post‐fracture. Our results showed that the LCN exhibited an exuberant outgrowth of canaliculi in the osteoporotic fractured bone at day 14 after LMHFV. LMHFV upregulated the E11, dentin matrix protein 1 (DMP1), and fibroblast growth factor 23 (FGF23), but downregulated sclerostin (Sost) in osteocytes. Moreover, LMHFV promoted mineralization with significant enhancements of Ca/P ratio, mineral apposition rate (MAR), mineralizing surface (MS/BS), and bone mineral density (BMD) in the osteoporotic group. Consistently, better healing was confirmed by microarchitecture and mechanical properties, whereas the enhancement in osteoporotic group was comparable or even greater than the normal group. This is the first report to reveal the enhancement effect of LMHFV on the osteocytes' morphology and functions in osteoporotic fracture healing.